2014
DOI: 10.1200/jco.2014.55.3628
|View full text |Cite
|
Sign up to set email alerts
|

Gemtuzumab Ozogamicin in Children and Adolescents With De Novo Acute Myeloid Leukemia Improves Event-Free Survival by Reducing Relapse Risk: Results From the Randomized Phase III Children's Oncology Group Trial AAML0531

Abstract: A B S T R A C T PurposeTo improve survival rates in children with acute myeloid leukemia (AML), we evaluated gemtuzumab-ozogamicin (GO), a humanized immunoconjugate targeted against CD33, as an alternative to further chemotherapy dose escalation. Our primary objective was to determine whether adding GO to standard chemotherapy improved event-free survival (EFS) and overall survival (OS) in children with newly diagnosed AML. Our secondary objectives examined outcomes by risk group and method of intensification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
433
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 407 publications
(451 citation statements)
references
References 46 publications
13
433
1
4
Order By: Relevance
“…This study could not be included since separate data in children were lacking. However, this study emphasizes the benefit of GO [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study could not be included since separate data in children were lacking. However, this study emphasizes the benefit of GO [38].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported on the incidence of neutropenia [4,26,30,38]. Median incidence of neutropenia was 98% with a range from 40% to 100%.…”
Section: Hematological Toxicitymentioning
confidence: 99%
“…Улучшение 3-летней бессобытийной выживаемости [26] у больных ОМЛ сопровождалось повышением смертности взрослых, а не детей, что послужило основанием для снятия препарата с продаж в США в 2010 г. У детей экспе-риментальная терапия была продолжена и отчеты по исследованиям дают шанс на возрождение препарата в комбинированной терапии ОМЛ [27,28]. Ведутся исследования с использованием анти-СD33 в виде биспецифических антител (анти-СD33 и СD3).…”
Section: перспективы оптимизации лечения острого мие-лобластного лейкозаunclassified
“…A children's oncology group study in newly diagnosed children with AML showed improved remission and event-free survival rates from the addition of a single GO dose of 3 mg/m 2 to standard intensive chemotherapy. 64 However, this effect was entirely counterbalanced by increased treatment toxicity, leading to no improvement in OS. In contrast, the French ALFA-0701 study conducted in older adults showed more promising results.…”
Section: Targeted Chemotherapy Deliverymentioning
confidence: 99%